2022
DOI: 10.2196/34904
|View full text |Cite|
|
Sign up to set email alerts
|

Culturally Safe eHealth Interventions With Aboriginal and Torres Strait Islander People: Protocol for a Best Practice Framework

Abstract: Background There is growing global evidence on the adoption and effectiveness of eHealth (including mobile health and telehealth) by First Nation peoples including Aboriginal and Torres Strait Islander people. Although there are frameworks to guide eHealth development, implementation, and evaluation, it is unknown whether they adequately encapsulate the health, cultural, and community-related priorities of Aboriginal and Torres Strait Islander people. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…There is a need for mHealth design to center end users within a co-designed approach with Indigenous people. There is recent work driving this agenda in an Australian context [ 60 ]. Allowing end users to suggest localized agenda setting through co-design may provide an opportunity for ownership, championship, and mitigation of barriers in mHealth implementation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for mHealth design to center end users within a co-designed approach with Indigenous people. There is recent work driving this agenda in an Australian context [ 60 ]. Allowing end users to suggest localized agenda setting through co-design may provide an opportunity for ownership, championship, and mitigation of barriers in mHealth implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Further preparatory work is likely required to prepare interventions shown to be effective in predominately non-Indigenous populations for ePCTs in Indigenous populations. Previous Indigenous health intervention research undertaken in Australia, Canada, the United States (US) and NZ has identified processes for investigating how to co-design, implement and evaluate interventions in Indigenous settings [20], adapting interventions prior to ePCT [21], how to ensure low resource environments are ready to implement an intervention within a ePCT [22], as well as targeting specific research processes, such as recruitment [23].…”
Section: Introductionmentioning
confidence: 99%